Зарубіжний досвід взаємодії територіальних органів поліції з громадськістю щодо забезпечення прав і свобод людини - Танько, А. В.; Tanko, A. V.; ORCID: https://orcid.org/0000-0001-8425-2202 (Юридична наука. - 2019. - № 2 (92). - С. 220-230, 2019)
Висвітлено провідне значення зарубіжного, насамперед європейського досвіду взаємодії територіальних органів поліції з громадськістю щодо забезпечення прав і свобод людини. Установлено, що продуктивним та вартим поширення у вітчизняній правозахисній діяльності з приводу організації позитивної співпраці поліції з населенням щодо захисту прав і свобод людини є загальний для багатьох зарубіжних країн підхід, що отримав назву Community Policing й передбачає співробітництво правоохоронних органів з населенням, ґрунтоване на поширенні сервісної моделі діяльності територіальних підрозділів поліції, підвищенні рівня соціальної відповідальності кожної особистості у справі забезпечення прав і свобод людини, підтриманні позитивного іміджу органів поліції тощо.

The article highlights the importance of foreign, primarily European experience of territorial police authorities’ interaction with the public on ensuring human rights and freedoms. Based on a retrospective analysis of the implementation process of police interaction with the public in the discourse of human rights development in foreign countries, it is proved that the spread of cooperation between state authorities and public groups in the world countries is based on ancient history and a significant ideological basis and is determined by the presence of some unresolved socio-legal problems in the state, which solution can contribute to a radical transformation of law enforcement. It is determined that an effective approach to the organization of positive cooperation between the police and the population on the protection of human rights and freedoms is a common approach for many foreign countries, called Community Policing and provides cooperation of law enforcement authorities with population, based on the service model extension of territorial police units, increasing the level of social responsibility of each person in ensuring human rights and freedoms, maintaining a positive image of the police, etc. A significant basis for the police cooperation extension with the community in Ukraine is the well-known Western programs of police interaction with the population (“Neighborhood Assistance”, “Stop the Criminal”, “Public Patrol”, “Administrative Assistance”, “Teams of Unsolved Cases”, “Victim Assistance” etc.). It was defined that in Ukraine the interaction of the National Police with the public in the field of human rights and freedoms has not developed in the same way as abroad, has a lack of legally regulated and tested mechanisms for establishing relations between territorial police and citizens, encouraging various human rights associations and communities until the partial solution of the tasks of territorial police units, etc.

Освещено ведущее значение зарубежного, прежде всего европейского опыта взаимодействия территориальных органов полиции с общественностью по обеспечению прав и свобод человека. Установлено, что продуктивным и достойным распространения в отечественной правозащитной деятельности по поводу организации положительного сотрудничества полиции с населением по защите прав и свобод человека является общий для многих зарубежных стран подход, получивший название Community Policing и предполагающий сотрудничество правоохранительных органов с населением, основанный на распространении сервисной модели деятельности территориальных подразделений полиции, повышении уровня социальной ответственности каждой личности в деле обеспечения прав и свобод человека, поддержании положительного имиджа органов полиции и т.п.
Foreign experience of territorial police authorities interaction with the public on ensuring human rights and freedoms
Зарубежный опыт взаимодействия территориальных органов полиции с общественностью по обеспечению прав и свобод человека
Танько, А. В. Зарубіжний досвід взаємодії територіальних органів поліції з громадськістю щодо забезпечення прав і свобод людини / Танько А. В. // Юридична наука. - 2019. - № 2 (92). - С. 220-230.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; поліція; police; полиция; зарубіжний досвід; foreign experience; зарубежный опыт; Україна. Ukraine. Украина; територіальні органи поліції; territorial police bodies; территориальные органы полиции; взаємодія поліції з населенням; interaction of the police with the population; взаимодействие полиции с населением; забезпечення прав і свобод людини; ensuring human rights and freedoms; обеспечение прав и свобод человека; Community Policing